Improving Corporate Reporting Based on an Intercompany Standard - R. G. Osipova (Учёт. Анализ. Аудит)
The article deals with the problem of standardization and unification of corporate reporting to generate reliable, transparent, high-quality information for stakeholders. In this case, the author used methods of logical analysis and generalization, logical and content analysis of reporting standards of Russian companies for distinct types of activity. During the study, the author identified a new content and basic principles for the development of an internal corporate reporting standard for a commercial organization. Also, the author formulated her position on the need for formation of named standard and indicated the advantages of its development. Application of this standard will create a unified methodological approach to the preparation of integrated corporate reporting; comply with the rules of internal requirements of interested users of corporate reporting; provide additional internal control over the main performance indicators of a commercial organization in the context of activities and check the quality of the entire organization; make the technology of generating integrated corporate reporting of commercial organizations more rational.